To improve the academy : (Anker Pub., 2004)
The development of students is a fundamental purpose of higher education and requires for its success effective advising, teaching, leadership, and management. Professional and Organizational Development Network in Higher Education (POD) fosters human development in higher education through faculty, instructional, and organizational development. A smart mix of big-picture themes, national developments, and examples of effective faculty development initiatives from a variety of schools, To Improve the Academy offers examples and resources for the enrichment of all educational developers. This annual volume incorporates all the latest need-to-know information for faculty developers and administrators.